Reinforcing Students’ Listening Comprehension through Video Based Learning Model for Secondary School (Scripta : English Department Journal, 2023)
This study was aimed at reinforcing listening comprehension through video-based learning models, educational videos for class IX students at SMPN 1 Jabiren Raya during the 2022/2023 academic year. The research used was classroom action research (CAR), all data were obtained through tests and questionnaires, then analyzed descriptively after being classified into related aspects in the questionnaire. The subjects of this study were class IX students of SMPN 1 Jabiren Raya for the 2022/2023 academic year. Researchers used cluster sampling to take samples to avoid subjectivity. The results of this study indicated that the use of educational video is effective in improving students' listening skills because the calculation results show that students' listening scores in the Pre-Test class of students who achieve the criterion of 4 students or percentage 43% with an average student score of 60. Then, students' listening scores in the Post Test class cycle I, students who reach the criteria of 21 students or a percentage of 75% with an average student score of 77. Finally, students' listening scores in the Post Test class cycle II, students who achieved the criterion of 27 students or a percentage of 97% with an average student score of 87. Second, related to the results of the analysis of student responses from the questionnaire, students' responses to the use of contextual video in listening practice were positive. Therefore, students can improve their listening skills. Related to student psychology, contextual videos increase students' motivation and interest in listening practice. This is related to the research in this study, based on the results of the pretest and posttest studies. Listening to students increased after implementing a video-based learning model, namely using educational videos. And based on the results of the student questionnaire showed a positive.
Keywords: Listening comprehension; Video based Learning Model